Data-driven predictive maintenance policy based on multi-objective optimization approaches for the component repairing problem. Issue 10 (3rd October 2021) - Pisacane, Ornella; Potena, Domenico; Antomarioni, Sara; Bevilacqua, Maurizio; Emanuele Ciarapica, Filippo; Diamantini, Claudia
Abstract : In systems with many components that are required to be constantly active, such as refineries, predicting the components that will break in a time interval after a stoppage may significantly increase their reliability. However, predicting the set of components to be repaired is a challenging task, especially when several conditions ( e.g. breakage probability, repair time and cost) have to be considered simultaneously. A data-driven predictive maintenance policy is proposed for maximizing the system reliability and minimizing the maximum repair time, considering both budget and human resources constraints. Therefore, a data-driven algorithm is designed for extracting component breakage probabilities. Then, two bi-objective optimization approaches are proposed for determining the set of components to repair. The former is based on the formulation of a bi-objective mixed integer linear programming model solved through the AUGMEnted ε -CONstraint (AUGMECON) method. The latter implements a bi-objective large neighbourhood search, outperforming the first approach.